COMMUNITY TRENDS TO CHOOSE THE SHARIA ECONOMIC SETTLEMENT AGREEMENT - Rabith Madah Khulaili Harsya (Diponegoro Law Review, 2018)
The tendency of people to choose the Sharia Economic Dispute Settlement Institution. The facts of the lack of sharia economic case submitted and decided by litigation and non-litigation institutions are the background of the research. This research is a kind of explorative research that uses qualitative approach to mengunggkap legal facts in the context of sharia economy. Data in the form of questionnaires / questionnaires processed only to describe the percentage percentage of the economic tendency of sharia community to choose dispute settlement institutions. This description is a preliminary data that lead researchers to explore the points of question needed in the interview between the results of quantitative data processing with the facts on the ground shows that people choose various options in solving the dispute sharia economy.